Abenteuer Männlichkeit. Adoleszenz in Wolfgang Herrndorfs Roman «Tschick»: [Adventure Manhood. Adolescence in Wolfgang Herrndorf’s Novel «Tschick»] (Studia theodisca, 2021)
This article deals with literary constructions of masculinity in Wolfgang Herrndorf’s novel Tschick. The focus is on male adolescence as represented by the characters in the text. The study is guided by the question of how the male socialisation of adolescents is narrated in the novel. Themes such as the search for identity, friendship, sexuality and being an outsider are addressed. The analysis is based on theoretical perspectives offered by masculinity studies, intersectional approaches of identity research as well as genre-related reflections on young adult fiction.